Predatory potential of Carabidae and Staphylinidae (Coleoptera) on the velvetbean caterpillar - Cividanes, Francisco Jorge; Ide, Sérgio; Ribeiro, Alex Antonio; Cividanes, Terezinha Monteiro dos Santos (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the predatory potential of adult Carabidae and Staphylinidae (Coleoptera) beetles on fourth‑instar larvae of the velvetbean caterpillar, in the laboratory. Initially, the capacity to consume one caterpillar during 24 hours was evaluated. For species that caused ≥80% mortality of the prey, the consumption rate was determined, by offering one caterpillar during 24 hours for four consecutive days. The carabids Calosoma granulatum, Cynthidia croceipes, Odontocheila nodicornis, and Pseudabarys sp. 1; the species of the Galerita, Scarites, and Tetracha genera; and the staphylinids Eulissus chalybaeus, Glenus cyanicollis, and Xenopygus sp. 2 show great predatory potential.